Analysis and forecast of the Tianjin industrial carbon dioxide emissions resulted from energy consumption. Issue 7 (9th August 2017) - Ge, Xiao-ling; Wang, Yang; Zhu, Hong-qing; Ding, Zequn
Abstract : This paper analyses the carbon dioxide emissions caused by industrial energy consumption of Tianjin from 2005 to 2012. The carbon emissions decomposition illustrated that the scale of production factor played a major role in the growth of Tianjin industrial carbon emissions and the average contribution of carbon emissions is up to 220.8975% in the statistical period; the intensity of energy factor played an important role in slowing down the growth of industrial carbon dioxide emissions. The average contribution of carbon emissions was −136.1994% in the statistical period. The prediction model based on carbon emissions data from industrial energy consumption from 2003 to 2012 reached a high accuracy, with an average error of 1.78% for stochastic impacts by regression on population, affluence, and technology (STIRPAT) model, 2.41% for the Logistic regression model and an average error of 1.54% for the grey model. This research can contribute to predict the carbon emission and through it some suggestions can be made.